2010
DOI: 10.1128/aem.01545-10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Antimicrobial Resistance and Virulence Genes inEnterococcusspp. and Characterization of Isolates from Broiler Chickens

Abstract: Enterococci are now frequent causative agents of nosocomial infections. In this study, we analyzed the frequency and distribution of antibiotic resistance and virulence genotypes of Enterococcus isolates from broiler chickens. Fecal and cecal samples from nine commercial poultry farms were collected to quantify total enterococci. Sixty-nine presumptive enterococci were isolated and identified by API 20 Strep, and their susceptibilities to antibiotics were determined. Genotypes were assessed through the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
93
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 39 publications
(59 reference statements)
21
93
3
4
Order By: Relevance
“…Our results are similar to the resistance profiles of lincomycin, tetracycline, penicillin, ciprofloxacin and tylosin in Enterococcus isolates from the environment of broiler and/or layer farms (Ruzauskas et al, 2009;Diarra et al, 2010;Šeputienė et al, 2012;Furtula et al, 2013). Moreover, in Poland, Różańska et al (2015) noted that the highest number of E. faecalis strains isolated from poultry meat were resistant to lincomycin (24 strains; 100%), the second-highest resistance was to tetracycline (21 strains; 87.5%), followed by tylosin (16 strains; 66.7%).…”
Section: Enterococcus Faecalis (%)supporting
confidence: 76%
See 1 more Smart Citation
“…Our results are similar to the resistance profiles of lincomycin, tetracycline, penicillin, ciprofloxacin and tylosin in Enterococcus isolates from the environment of broiler and/or layer farms (Ruzauskas et al, 2009;Diarra et al, 2010;Šeputienė et al, 2012;Furtula et al, 2013). Moreover, in Poland, Różańska et al (2015) noted that the highest number of E. faecalis strains isolated from poultry meat were resistant to lincomycin (24 strains; 100%), the second-highest resistance was to tetracycline (21 strains; 87.5%), followed by tylosin (16 strains; 66.7%).…”
Section: Enterococcus Faecalis (%)supporting
confidence: 76%
“…In contrast to Diarra et al (2010) and Furtula et al (2013), we found a high sensitivity to penicillin antibiotics in 911 of the isolated Enterococcus strains. Moreover, E. faecalis and E. faecium strains isolated from affected broilers, layers and turkeys were susceptible to ampicillin.…”
Section: Enterococcus Faecalis (%)mentioning
confidence: 54%
“…This is because this waste is rich in antibiotic residues (63), antibiotic-resistant bacteria, and antibiotic resistance genes (ARGs) (10,17,23,29), which can enter the environment through disposal practices (14). Growing evidence further shows that animal waste, including poultry litter, contains various mobile genetic elements (MGEs) harboring ARGs (8,10,11,40), which facilitate the spread of ARGs to soil microbial communities when animal waste is applied onto agricultural soils (30).…”
mentioning
confidence: 99%
“…Resistance to these antibiotics has frequently been observed in bacterial isolates from poultry litter (10,17,23,29). Furthermore, some MGEs simultaneously carry genes encoding tetracycline resistance (Tc r ; tet) and MLS B resistance (erm) (13,49) and facilitate the dissemination of resistance to these antibiotics among environmental, commensal, and clinical bacteria (48).…”
mentioning
confidence: 99%
“…A frequência do gene ace em ambos os grupos está de acordo com outros estudos que avaliaram a presença deste gene em amostras de swabs cloacais de frangos. Diarra et al (2010) detectaram o gene ace em todos os E. faecalis isolados de frangos pesquisados. Olsen et al (2011) pesquisaram o gene ace em isolados clínicos e de frangos e detectaram a presença do gene em todas as amostras pesquisadas.…”
Section: Discussionunclassified